Systematic review of innovation design contests for health: spurring innovation and mass engagement. Issue 4 (27th September 2017) - Pan, Stephen W; Stein, Gabriella; Bayus, Barry; Tang, Weiming; Mathews, Allison; Wang, Cheng; Wei, Chongyi; Tucker, Joseph D
Abstract : We undertook a systematic review evaluating the effectiveness and cost of health-focused innovation design contests. We followed Cochrane guidance and systematically searched eight databases. Articles were included if they reported an open contest focused on improving health, required participants submit finished design solutions and contained a prize structure. We searched 3579 citations, identifying 29 health-focused innovation design contests which collectively received 15494 contest submissions. Contests solicited submissions worldwide (7) and exclusively from North America (13), Asia (4), Africa (2), Australia (2) and Europe (1). Submissions per contest ranged from 3 to 11354 (median of 73). Contest entrants were tasked with helping develop health promotion messages (HPM) (25) and improve predictive clinical models, protocols and/or algorithms (4). Two types of contests emerged—those focused on high-quality, innovative outcomes and those focused on the process of mass community engagement. All outcome-oriented contests had innovation design contest solutions equivalent or superior to the comparator (100%; 7/7). Two of two studies found that innovation design contests saved money (100%; 2/2). Five of seven process-oriented contests concluded the contest improved at least one health indicator (71%; 5/7). Innovation design contests are an effective way to solicit innovative solutions to health problems and spur mass community engagement.